FY2019 Brazil Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The country opinion survey in Brazil assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Brazil perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral and bilateral agencies, media, academia, the private sector, and civil society in Brazil on: (1) their views regarding the general environment in Brazil; (2) their overall attitudes toward the WBG in Brazil; (3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Brazil; and (4) their perceptions of the WBG’s future role in Brazil.